Cardiovascular Complications of Diabetic Kidney Disease - Pálsson, Ragnar (2014)
Diabetic nephropathy is the most common cause of chronic kidney disease and represents a large and ominous public health problem. Patients with diabetic kidney disease have exceptionally high rates of cardiovascular morbidity and mortality. In fact, the excess mortality among patients with diabetes appears to be largely limited to the subgroup with kidney disease and explained by their high burden of cardiovascular disease. The mechanisms underlying the strong association between diabetic kidney disease and various forms of cardiovascular disease are poorly understood. Traditional risk factors for cardiovascular disease, although prevalent among those with diabetes, do not fully account for the heightened risk observed. Despite their susceptibility to cardiovascular disease, patients with chronic kidney disease are less likely to receive appropriate risk factor modification than the general population. Moreover, as patients with chronic kidney disease have commonly been excluded from major cardiovascular trials, the evidence for potential treatments remains limited. Currently, mainstays of treatment for diabetic kidney disease include blockade of the renin-angiotensin-aldosterone system, and control of hypertension, hyperglycemia and dyslipidemia. Increased awareness of the vulnerability of this patient population and more timely interventions are likely to improve outcomes, while large evidence gaps are filled with newer studies.